A bibliometric analysis on sustainable investment in financial markets - Wang, Yi Jie; Choo, Wei Chong; Ng, Keng Yap; Lin, Yi Huan (Universiti Putra Malaysia, 2024)
With the appearance of potential risks and benefits brought about by environmental, social, and governance factors, various industries are aware of the importance of sustainable investment. Undeniably, sustainable investing has become an important force for change in different industries, especially in financial markets. However, the current state of research in this field remains unexplored, with the specific research focus and the role of countries in economic globalization and sustainable development remaining undocumented. To address this issue, this article presents a bibliometric analysis of sustainable investments in financial markets using data extracted from the Scopus database. The study explores the current state of research on sustainable investing in financial markets and identifies potential directions for future research by analysing a total of 1,794 academic articles published in leading finance and sustainability journals between 1982 and April 2023. This analysis further examines the relationship between national academic collaboration and key research themes. Analysis of the results shows that the United States, China and the United Kingdom rank among the top three in the number of publications in the field of sustainable investment research. Developing countries such as China and India are also gradually increasing their attention in this field and gradually assuming corresponding responsibilities. The keyword co-occurrence analysis further highlights the vital role of the core concepts of “Investment”, “Commerce”, “Costs” and “Climate Change” and “Energy policy” in sustainable investment research and practice. The findings of this quantitative bibliographic analysis will be of significant value to researchers, policymakers and practitioners interested in sustainable investing and its role in shaping the future of finance.